The Action Between Linguistic Argumentation and Theatrical Performance: The Play 'Jaban' as a Model" - Adnan Abboud, Researcher. Hazem; Abboud Al-Nakhil, Assist.Prof. Dr. Hassan; Abdel Wahab Abdel Zahr, Assist. Prof Dr. Hassanein (Basra studies journal, 2024)
Argumentation is one of the subjects that has marked an important milestone in linguistic studies and the effectiveness of verbal performance. Since language is the foundation upon which the actor relies to produce the system of discourse through the energy and effectiveness of theatrical performance, it interacts with other elements of the production, starting from the text—the substance of language—to the overall composition of the discourse based on a combination of auditory, verbal, kinetic, and visual elements. The significance of this research lies in highlighting an important aspect of expressive language, which is argumentation and its significant connection to linguistic studies focusing on pragmatics, rhetoric, and communication. This results in new discoveries in interpreting theatrical performance through the text and acting performance. The first chapter, representing the methodological framework, includes the research problem, objectives, scope, terminology, and definitions. The second chapter, the theoretical framework, comprises two sections: the first deals with argumentation in linguistic studies, and the second discusses the argumentative action in acting. The researcher then identified several indicators. The third chapter, which is procedural, includes the research procedures and sample analysis. The fourth chapter presents the findings and conclusions, followed by a bibliography of sources and references